Domestic darkness : an insider's account of the January 6 Insurrection, and the future of right-wing extremism - Farnam, Julie (Ig Publishing, 2024)
"After being named Assistant Director of Intelligence for the Capitol Police just days before the 2020 election, Julie Farnam warned its leadership of the upcoming insurrection, sharing that "Congress itself is the target on the 6th." Tragically, her warnings were ignored. DOMESTIC DARKNESS takes us inside the explosive events of January 6, 2021, exposing how the Capitol Police disregarded intelligence about the right-wing extremists who would seize the capitol on the fateful day. In addition to offering a harrowing view of what it was like on the ground, watching the violence unfold and knowing it could have been prevented, DOMESTIC DARKNESS also examines the specific groups and ideologies, such as the Oath Keepers, Proud Boys, QAnon and white supremacists, who were central to the events of January 6 and who, emboldened by Donald Trump and other right-wing leaders, continue to be a threat to our democracy. The book also explores the changes within Capitol Police in the wake of the insurrection---many introduced by Farnam after she was named Acting Director---and, critically for our country, how to address future dangers from domestic terrorism. With the 2024 presidential election just around the corner, we need to seriously examine the lessons January 6 taught us to ensure something like that never happens again"--Dust jacket flap.